2021
DOI: 10.1021/acs.est.1c05006
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Transfer and Toxicity of (Mixtures of) Ag and TiO2 Nanoparticles in the Lettuce–Terrestrial Snail Food Chain

Abstract: The increasing application of biosolids and agrochemicals containing silver nanoparticles (AgNPs) and titanium dioxide nanoparticles (TiO 2 NPs) results in their inevitable accumulation in soil, with unknown implications along terrestrial food chains. Here, the trophic transfer of single NPs and a mixture of AgNPs and TiO 2 NPs from lettuce to snails and their associated impacts on snails were investigated. Both AgNPs and TiO 2 NPs were trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
2
18
1
Order By: Relevance
“…22 Previous reports have shown that Ag can accumulate in edible tissues of leafy vegetables either via root exposure or foliar exposure. For example, Wu et al 32 reported that Ag can be taken up by hydroponically cultivated lettuce ( L. sativa L.). By using inductively coupled plasma-mass spectrometry (ICP-MS), Ag (1 mg kg −1 ) was detected in the leaves of lettuce exposed to 0.75 mg L −1 AgNPs, which can be further transferred to lettuce's consumer snails.…”
Section: General Review On the Phytotoxicity Of Agnpsmentioning
confidence: 99%
“…22 Previous reports have shown that Ag can accumulate in edible tissues of leafy vegetables either via root exposure or foliar exposure. For example, Wu et al 32 reported that Ag can be taken up by hydroponically cultivated lettuce ( L. sativa L.). By using inductively coupled plasma-mass spectrometry (ICP-MS), Ag (1 mg kg −1 ) was detected in the leaves of lettuce exposed to 0.75 mg L −1 AgNPs, which can be further transferred to lettuce's consumer snails.…”
Section: General Review On the Phytotoxicity Of Agnpsmentioning
confidence: 99%
“…The environmental impact of this nanoparticulate metal oxide should not be underestimated, not only because it can have an adverse effect on single organisms and their ecosystem functioning, but also because its potential bioaccumulation, biomagnification and transfer through the food chain may very well, in the end, impact multiple species [ 20 , 66 , 68 , 69 ]. The complex interconnectivity between different trophic levels within and, indeed, between different ecosystems means that next to none are immune to TiO 2 contamination.…”
Section: Tio 2 Nps and Other Eukaryotes—toxic Or Not?mentioning
confidence: 99%
“…The impact of TiO 2 is not limited only to aquatic vegetation and its toxic effects have also been explored in terrestrial plants, where accumulation/uptake appears to occur via their root system in a concentration dependent manner [ 13 , 69 , 92 ]. Although detrimental effects of TiO 2 should always be of concern (e.g., [ 73 ]), it is apparent that TiO 2 can induce some changes that could be considered beneficial, such as an increase in chlorophyll content and connected plant weight/growth, at least at lower concentrations [ 13 , 14 , 15 , 16 , 105 ], which is particularly interesting in agriculture.…”
Section: Tio 2 Nps and Other Eukaryotes—toxic Or Not?mentioning
confidence: 99%
“…27 In soil ecosystems, animals form a complex food web through predator−prey relationships. 28 Many contaminants (e.g., heavy metals 29 and nanoparticles 30 ) have been found to transmit through the soil food chain and affect the health of organisms at high trophic levels. In terms of ARGs, microcosm experiments have shown that ARGs from pig manure can be transmitted through the food chain into the microbiomes of high-trophic animals.…”
Section: Introductionmentioning
confidence: 99%